Chapter Analisi del questionario per la rilevazione degli obiettivi conseguiti dal TDDI - Grilli, Antonella (Strumenti per la didattica e la ricerca, 2022)
In August 2021, a questionnaire was sent to all those who had participated in the presentation meetings of the Integrated Digital Direct Internship Experimental Project (TDDI), a questionnaire to identify the objectives achieved. The survey was sent to 99 schools, 238 subjects including teachers, trainees and headteachers and to 18 university tutors of the Course of Studies in Primary Education at the University of Florence. The survey obtained 186 responses and allowed an initial evaluation of the results in relation to the target actually involved and informed of the experimental path. The focus is to detect the level of satisfaction of the subjects actually involved and to highlight how much TDDI can meet the expectations of school managers, teachers, students.